Facile surfactant-free synthesis and characterization of Fe3O4@3-aminophenol–formaldehyde core–shell magnetic microspheres. Issue 2 (23rd September 2014) - Zhao, Jianming; Luque, Rafael; Qi, Wenjing; Lai, Jianping; Gao, Wenyue; Hasan Shah Gilani, Muhammad Rehan; Xu, Guobao
Abstract : Fe3 O4 @3-aminophenol–formaldehyde (Fe3 O4 @APF) core–shell resin polymer magnetic nanocomposites were fabricated by the polymerization of 3-aminophenol and formaldehyde as efficient absorbants for methyl blue. Abstract : Fe3 O4 @3-aminophenol–formaldehyde (Fe3 O4 @APF) core–shell resin polymer magnetic nanocomposites were synthesized using a straightforward surfactant-free methodology. The shell quickly formed within 5 min and could be easily size tunable in the range from 15 to 137 nm by changing the concentrations of 3-aminophenol and formaldehyde. The morphology, composition and magnetic properties of the resulting magnetic microspheres were characterized by scanning electron microscopy, X-ray diffraction, Fourier transform infrared spectroscopy, and thermogravimetric analysis measurements. The magnetic microspheres were uniform in morphology and can be converted into Fe3 O4 @carbon magnetic nanocomposites because of their excellent thermal stability. Moreover, Fe3 O4 @APF magnetic microspheres have excelling adsorption properties in the removal of methyl blue.